2018
DOI: 10.1002/cpdd.454
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Pharmacokinetics and Pharmacodynamics of Bococizumab Following a Single Subcutaneous Injection Using Drug Substance Manufactured at Two Sites or Administration via Two Different Devices

Abstract: The pharmacokinetics (PK) and pharmacodynamics (PD) of bococizumab, a proprotein convertase subtilisin/kexin type 9 (PCSK9) inhibitor, were compared following a single 150-mg subcutaneous dose administered to healthy subjects (n = 156-158/arm) via: (1) a prefilled syringe (PFS) using drug substance (DS) manufactured by Pfizer, (2) a PFS using DS manufactured by Boehringer Ingelheim Pharma, (3) a prefilled pen using DS manufactured by Pfizer (NCT02458209). Blood samples were collected for 12 weeks postdose. Saf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Immunogenicity assessments were done regularly in phase II and III studies. Primary observations from these clinical studies have been presented in full elsewhere 11–18 …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Immunogenicity assessments were done regularly in phase II and III studies. Primary observations from these clinical studies have been presented in full elsewhere 11–18 …”
Section: Methodsmentioning
confidence: 99%
“…All participants provided written, informed consent. Full detail is given in the primary publications 11–18 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Drugs administered trans dermally exhibit high bioavailability as they avoid gastrointestinal processing and the first-pass metabolic process (Nagarkar et al, 2020 ). However, raw drugs injections under the skin usually result in a sharp rise in blood plasma concentrations within the early stage of administration, and dramatically decreases after a max concentration is reached, thereby effectively pushing the drug concentration beyond its useful therapeutic window (Kagan, 2014 ; Wang et al, 2019 ). In the case of bee venom solution injections, as concentration levels increase sharply, the injection method can induce sharp and painful sensations and other adverse effects (Chen et al, 2016 ; Burzyńska & Piasecka-kwiatkowska, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Bococizumab is a humanized IgG2Δa mAb targeting the LDL receptor-binding domain of PCSK9 [12]; it has been studied in phase I–III clinical studies, and has been found to both lower LDL-C and reduce cardiovascular event rates [1321]. In November 2016, clinical development of bococizumab was discontinued as a result of the emerging clinical profile observed from the SPIRE (Studies of PCSK9 Inhibition and the Reduction of vascular Events) phase III lipid-lowering program [15, 22].…”
Section: Introductionmentioning
confidence: 99%